2019
DOI: 10.1002/anie.201903882
|View full text |Cite
|
Sign up to set email alerts
|

Morphology‐Engineered Highly Active and Stable Ru/TiO2 Catalysts for Selective CO Methanation

Abstract: Ru/TiO 2 catalysts exhibit an exceptionally high activity in the selective methanation of CO in CO 2 -and H 2 -rich reformates,b ut suffer from continuous deactivation during reaction. This limitation can be overcome through the fabrication of highly active and non-deactivating Ru/TiO 2 catalysts by engineering the morphology of the TiO 2 support. Using anatase TiO 2 nanocrystals with mainly {001}, {100}, or {101} facets exposed, we show that after an initial activation period Ru/TiO 2 -{100} and Ru/TiO 2 -{10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 32 publications
7
51
0
3
Order By: Relevance
“…It is quite surprising and interesting that on 1Ru/a-TiO 2 catalyst CO cannot be hydrogenated into CH 4 as Ru/TiO 2 is usually regarded as one of the best candidates for selective methanation of CO. [31] Thea dsorption and subsequent dissociation of CO on catalyst is usually regarded as acritical step in CO hydrogenation to methanation. [32] However, am icrocalorimetry measurement of the CO adsorption suggested that the adsorption strengths on the two samples are similar ( % 145 kJ mol À1 ), Figure S12.…”
Section: Resultsmentioning
confidence: 99%
“…It is quite surprising and interesting that on 1Ru/a-TiO 2 catalyst CO cannot be hydrogenated into CH 4 as Ru/TiO 2 is usually regarded as one of the best candidates for selective methanation of CO. [31] Thea dsorption and subsequent dissociation of CO on catalyst is usually regarded as acritical step in CO hydrogenation to methanation. [32] However, am icrocalorimetry measurement of the CO adsorption suggested that the adsorption strengths on the two samples are similar ( % 145 kJ mol À1 ), Figure S12.…”
Section: Resultsmentioning
confidence: 99%
“…Semiconductor, such as TiO 2 , attracted the attention of many researchers due to its versatile advantages involving stable catalytic performance and low cost [28][29][30]. It has been widely reported that the introduction of transition metal [31][32][33] or noble metal nanoparticles [34][35][36] to TiO 2 support is beneficial for electron transfer in the photochemical reaction process. For instance, Farnood et al demonstrated a novel Bi and Pt co-modified TiO 2 catalyst for the photo-oxidation of lignin under solar light for the generation of guaiacol, vanillic acid, vanillin and 4-phenyl-1-buten-4-ol [37].…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…It is widely accepted that the photodegradation efficiency of the catalyst is greatly affected by its bandgap, morphology, crystallinity, defects, and size [3,17,18]. Morphology engineering is a crucial factor in the synthesis of an efficient and stable catalyst [19]. Up to now, different morphologies of MoS 2 such as nanosheets, nanospheres, and nanoflowers are successfully synthesized by the hydrothermal route [20][21][22].…”
Section: Introductionmentioning
confidence: 99%